Search for heavy narrow dilepton resonances in $pp$ collisions at $\sqrt{s}=7$ TeV and $\sqrt{s}=8$ TeV - CMS collaboration (2203 authors) (2013)
An updated search for heavy narrow resonances decaying to muon or electron pairs using the CMS detector is presented. Data samples from pp collisions at sqrt(s) = 7 TeV and 8 TeV at the LHC, with integrated luminosities of up to 5.3 and 4.1 inverse femtobarns, respectively, are combined. No evidence for a heavy narrow resonance is observed. The analysis of the combined data sets excludes, at 95% confidence level, a Sequential Standard Model Z'[SSM] resonance lighter than 2590 GeV, a superstring-inspired Z'[psi] lighter than 2260 GeV, and Kaluza-Klein gravitons lighter than 2390 (2030) GeV, assuming that the coupling parameter k/M-bar[Pl] is 0.10 (0.05). These are the most stringent limits to date.